2018
DOI: 10.1111/ijfs.13882
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sarcoplasmic protein phosphorylation on glycolysis in postmortem ovine muscle

Abstract: Protein phosphorylation is a key modulator in glycolysis metabolism and regulates the activity of glycometabolic enzymes. The phosphorylation levels of sarcoplasmic proteins were investigated in relationship to the glycolysis rate in postmortem ovine muscle in the present study. The global phosphorylation levels of sarcoplasmic proteins increased early postmortem and then decreased afterwards in postmortem ovine muscle. Protein bands of different phosphorylation levels were identified as glycometabolism‐relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…After 1 day's storage, the phosphorylation levels of glucose‐6‐phosphate isomerase and pyruvate kinase (band 10) were higher at 25 °C. Consistently, Chen et al . reported that the phosphorylation levels of glucose‐6‐phosphate isomerase and pyruvate kinase were positively correlated with the glycolytic rate.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…After 1 day's storage, the phosphorylation levels of glucose‐6‐phosphate isomerase and pyruvate kinase (band 10) were higher at 25 °C. Consistently, Chen et al . reported that the phosphorylation levels of glucose‐6‐phosphate isomerase and pyruvate kinase were positively correlated with the glycolytic rate.…”
Section: Resultsmentioning
confidence: 53%
“…14 A negative correlation between the phosphorylation level of adenylate kinase isoenzyme 1 (band 18) and ATP content indicated that phosphorylated adenylate kinase isoenzyme 1 may contribute to muscle rigor and contraction. In band 10, the phosphorylation level changes at 25 and 15 ∘ C were inconsistent with those at 4 and −1.5 ∘ C. After 1 day's storage, the phosphorylation levels of glucose-6-phosphate isomerase and pyruvate kinase (band 10) were higher at 25 ∘ C. Consistently, Chen et al 17 reported that the phosphorylation levels of glucose-6-phosphate isomerase and pyruvate kinase were positively correlated with the glycolytic rate. Moreover, Schwägele et al 33 showed that the phosphorylated isoform of pyruvate kinase can have higher acid stability, indicating that phosphorylated pyruvate kinase can maintain high activity at low pH.…”
Section: Analysis Of the Phosphorylation Levels Of Individual Bands Amentioning
confidence: 77%
See 1 more Smart Citation
“…Glycolysis is a multistep conversion of glucose to pyruvate catalyzed by specific enzymes. Most of these enzymes, such as glycogen phosphorylase, phosphofructokinase, and pyruvate kinase, are identified as phosphoproteins and affect meat quality characteristics by regulating glycolysis cycle, protein degradation, and structure of meat (Chen et al., 2018; Huang, Larsen, et al., 2011; Wu et al., 2015; Scheffler & Gerrard, 2007; Li et al., 2012). As the core metabolic pathway in postmortem muscle, glycolysis is highly relevant to ultimate meat quality (Dalrymple & Hamm, 1975; Lomiwes, Farouk, Wu, & Young, 2014).…”
Section: Protein Phosphorylationmentioning
confidence: 99%
“…Meanwhile, GAPDH, which is an enzyme involved in glycolysis, was shown to be hyperphosphorylated after the Al 3 + treatment (Fig 4). The enzyme was activated by phosphorylation [48], and then, Al 3+ stress accelerated the glycolytic rate. Citric acid metabolism, as part of the tricarboxylic acid (TCA) cycle, occurs in mitochondria.…”
Section: Dpps Promotes Citric Acid Synthesis Under Al 3+ Stressmentioning
confidence: 99%